2021
DOI: 10.1155/2021/9012887
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hyponatremia and Peripheral Neuropathy in Patients with Diabetes

Abstract: Objectives. Hyponatremia is a common complication of diabetes. However, the relationship between serum sodium level and diabetic peripheral neuropathy (DPN) is unknown. This study was aimed at investigating the relationship between low serum sodium level and DPN in Chinese patients with type 2 diabetes mellitus. Methods. A retrospective study was performed on 1928 patients with type 2 diabetes between 2010 and 2018. The multivariate test was used to analyze the relationship between the serum sodium level and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…A 2019 review found that elevated fracture risk observed in patients with T2D may be in part a consequence of diabetic peripheral neuropathy (DPN) ( 48 ). Another cross-sectional study of Chinese patients with T2D detected an independent association between low-normal serum sodium levels and DPN incidence ( 49 ). Accordingly, low-normal serum sodium levels may contribute to muscle loss, neuropathy, and decreased bone turnover in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 review found that elevated fracture risk observed in patients with T2D may be in part a consequence of diabetic peripheral neuropathy (DPN) ( 48 ). Another cross-sectional study of Chinese patients with T2D detected an independent association between low-normal serum sodium levels and DPN incidence ( 49 ). Accordingly, low-normal serum sodium levels may contribute to muscle loss, neuropathy, and decreased bone turnover in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria of DPN varied in different studies [ 9 , 19 , 20 , 21 ]. Our study confirmed the diagnosis of DPN with nerve conduction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] It is also supported by studies showing changes in nerve conduction studies and F-wave latencies in hyponatremia. [ 6 7 ] To the best of our knowledge and after an exhaustive review of the literature, it is noted that worsening of trigeminal neuralgic pain due to hyponatremia has not been reported before. Our patient improved significantly within 72 h of correction in sodium levels.…”
Section: Introductionmentioning
confidence: 99%